Feasibility of different meningioma delineation approaches on (18F)SiTATE PET/CT imaging - Kunte, Sophie Carina; Unterrainer, Lena M.; Lindner, Simon; Holzgreve, Adrien; Kunz, Wolfgang G.; Winkelmann, Michael; Nitschmann, Alexander; Jurkschat, Klaus; Wängler, Carmen; Wängler, Björn; Schirrmacher, Ralf; Belka, Claus; et al. (Discover oncology, 2025)
Somatostatin receptor (SSTR)-targeted PET is valuable for meningioma imaging due to high SSTR expression. [18F]SiTATE, a novel tracer, is not only promising for imaging neuroendocrine tumors but also for meningiomas. Standardized delineation methods on [18F]SiTATE PET are lacking. This study correlates CT-based volumes with PET-based delineation approaches to identify a threshold for standardized [18F]SiTATE PET volume assessment.
Online veröffentlicht: 14. November 2025
Im Titel ist (18F) in eckigen Klammern geschrieben und hochgestellt
Gesehen am 29.01.2026